Hubungan Koordinasi Mata Tangan, Kelincahan Dan Keseimbangan Terhadap Kemampuan Dribble Bolabasket - Sahabuddin (Journal Coaching Education Sports, 2020)
This study aims to determine the relationship between hand eye coordination, agility, and balance with dribbling in basketball games. This research is a descriptive research. The population of this study were all male students of SMK Negeri 7 Makassar with a total sample of 40 people selected by random sampling. The data analysis technique used is the correlation analysis technique using the SPSS version 17.00 system at a significant level of 95% or 0.05. Starting from the results of data analysis, this study concludes that: (1) hand eye coordination has a significant relationship with dribbling in basketball games for students of SMK Negeri 7 Makassar, proven ro = -0,668 (P = 0,000 <a0,05); (2) agility has a significant relationship with dribble in the basketball game for students of SMK Negeri 7 Makassar, proven to be ro = 0.830 (P = 0.000 <a0.05); (3) balance has a significant relationship with dribble in basketball games for students of SMK Negeri 7 Makassar, proven ro = -0,828 (P = 0,000 <a0,05); and (4) hand eye coordination, agility, and balance have a significant relationship with dribbling in basketball games for students of SMK Negeri 7 Makassar, it is proven that Ro = 0.875 (P = 0.000 <a0.05)